IMPLEMENTASI TEKNIK ECOPRINT UNTUK MENINGKATKAN KREATIVITAS ANAK USIA DINI DI KB STRAWBERRY SURAKARTA TAHUN PELAJARAN 2023/2024: IMPLEMENTASI TEKNIK ECOPRINT UNTUK MENINGKATKAN KREATIVITAS ANAK USIA DINI DI KB STRAWBERRY SURAKARTA TAHUN PELAJARAN 2023/2024 - Titi Fatimah Titi; M. Hery Yuli Setiawan; Oka Irmade (Widya Wacana: Jurnal Ilmiah, 2024)
The aim of this research is to enhance early childhood creativity through the implementation of ecoprint techniques in craton class (group B) KB Strawberry Surakarta Learning Year 2023/2024. This research was conducted using the Class Action Research (PTK) method that uses the modification of Kemis and McTaggart models. The subjects in the study are 14 children and the object of the study is to enhance the creativity of children through the implementation of ecoprint techniques. Data collection techniques are done by means of observation, interview, and documentation. Data analysis techniques use quantitative descriptives, the minimum indicator set in this study is 85% of 14 with evaluation criteria evolving according to expectations. Based on the results of the research indicators of implementation of ecoprint techniques children's creativity develops very well, as many as 10 children of 71.43% are on criteria of development very good, and 4 children develop as expected of 28.57%. (group B). Keywords: Creativity, Ecoprint Techniques